2014
DOI: 10.1055/s-0034-1383307
|View full text |Cite
|
Sign up to set email alerts
|

5β,19-Epoxycucurbitane Triterpenoids from Momordica charantia and Their Anti-Inflammatory and Cytotoxic Activity

Abstract: Five new 5β,19-epoxycucurbitane triterpenoids, taikugausins A-E (1-5), together with 5β,19-epoxy-25-methoxycucurbita-6,23-diene-3β,19-diol (6), have been isolated and characterized from the 70 % EtOH extract of the fresh fruits of Momordica charantia. The chemical structures of compounds 1-6 were elucidated on the basis of extensive spectroscopic analyses, especially 2D NMR (HMQC, HMBC, and NOESY) experiments and HRESIMS data. The relationship between NMR chemical shifts and the configuration of C-19 with an O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 19 publications
2
23
0
2
Order By: Relevance
“…M. charantia was found to improve the biological responses against inflammation in rats with sepsis (Chao et al, 2014). Other authors also report the anti-inflammatory activity of this plant (Nagarani et al, 2014;and Liaw et al, 2015).…”
Section: Anti-inflammatory Activitymentioning
confidence: 92%
See 1 more Smart Citation
“…M. charantia was found to improve the biological responses against inflammation in rats with sepsis (Chao et al, 2014). Other authors also report the anti-inflammatory activity of this plant (Nagarani et al, 2014;and Liaw et al, 2015).…”
Section: Anti-inflammatory Activitymentioning
confidence: 92%
“…Ma et al (2014) 5β,19-epoxycucurbitane triterpenoids, Liaw et al (2015) Karavilagenin F, karaviloside XII, karaviloside XIII, momordicine VI, momordicine VII, momordicine VIII Zhao et al (2014) temperature, reducing the incidence of degradation of the product; in some cases subsequent purification steps are not necessary (Bagheri et al, 2014;Conde et al, 2014;Nguyen et al, 2015).…”
Section: Identified Terpenoids Referencementioning
confidence: 99%
“…Buah pare juga mengandung senyawa yang memiliki aktivitas sitotoksik seperti taikuguasin C, taikuguasin D, charantagenin D, goyaglikosid, charantagenin E, momordikosid K, asam 3,7diokso-23,24,25,26,27-pentanorcucurbit-5en-22-oat,25,26,27-trinorcucurbit-5-ene-3,7,23-trione, cucurbitacin B dan stigmasta-7,25(27)-dien-3β-ol. Taikugausin C serta taikugausin D yang diperoleh dari ekstrak etanol buah pare memiliki aktivitas sitotoksik terhadap sel kanker payudara MCF-7 masingmasing memiliki ED50 42,60 µM dan 42,66 µM (Liaw et al, 2015). Charantagenin D dan goyaglikosid diperoleh dari ekstrak etanol buah pare memiliki aktivitas sitotoksik yang lebih poten terhadap sel kanker glioblastoma U87 daripada charantagenin E, momordikosid K dan stigmasta-7,25(27)-dien-3β-ol, charantagenin D memiliki IC50 sebesar 1,08 µmol/L dan goyaglikosid sebesar 0,19 µmol/L (Wang et al, 2012).…”
Section: Pendahuluanunclassified
“…Further in 2015, Liaw et al [48] reported the isolation and identification of five new 5β,19 epoxycucurbitane triterpenoids, taikuguasins (A–E) along with 5β,19-epoxy-25-methoxycucurbita-6,23-diene-3β,19-diol from the ethanolic extract of fresh M. charantia fruits (Taiwanese variety). These compounds were screened for their anti-inflammatory and cytotoxic activity; out of which, taikuguasin C and D showed significant inhibition of lipopolysaccharide (LPS)-induced NO production in the mouse macrophage RAW 264.7 cell line as well as showed significant cyto-toxic effects (in MTT assay) against MCF-7 (breast cancer), HepG2 (hepatocellular cancer), HEp-2 (laryngeal cancer), and WiDr (colon cancer) cells [48].…”
Section: Bioassay Guided Fractionations Of Bitter Melon (M Charanmentioning
confidence: 99%
“…These compounds were screened for their anti-inflammatory and cytotoxic activity; out of which, taikuguasin C and D showed significant inhibition of lipopolysaccharide (LPS)-induced NO production in the mouse macrophage RAW 264.7 cell line as well as showed significant cyto-toxic effects (in MTT assay) against MCF-7 (breast cancer), HepG2 (hepatocellular cancer), HEp-2 (laryngeal cancer), and WiDr (colon cancer) cells [48]. …”
Section: Bioassay Guided Fractionations Of Bitter Melon (M Charanmentioning
confidence: 99%